The Effectiveness of a Proposed Enrichment Program Based on Problem-Solving and Problem Posing in Developing the Ability of Mathematical Reasoning and Sense-Making among Grade Ten High Achievers - Salama S. Al Badri; Reda A. Al Sayed (Journal of Educational and Psychological Studies, 2017)
This study aimed to reveal the effectiveness of a proposed enrichment program based on problem-solving and problem posing in developing the ability of the mathematical reasoning and sense making among students of high achievement. To achieve this goal, an enrichment training program was designed to focus on a set of mathematical ideas and skills in mathematics using problem-solving and problem- posing strategies to solve and pose non-routine mathematical problems for students of high achievement to develop their mathematical reasoning and sense making ability. The researcher designed a test to measure the mathematical reasoning and sense making. In addition, the Test of Mathematical Abilities (TOMA-3) was used to measure the students' mathematical abilities before the experiment. The sample of the study consisted of 63 grade ten high achievers randomly selected from South Batinah governorate, which was divided into control and experimental groups. For testing the study hypothesis, data was analyzed by analysis of covariance (ANCOVA) in which eta squared was obtained. The results showed that the proposed program was effective and the mathematical reasoning and sense making skills were highly achieved.